2004
DOI: 10.1152/ajpheart.00588.2003
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of LV diastolic function during atrial fibrillation: beat-to-beat analysis in acute dog experiments

Abstract: N. Mazgalev. Determinants of LV diastolic function during atrial fibrillation: beat-to-beat analysis in acute dog experiments. Am J Physiol Heart Circ Physiol 286: H145-H152, 2004. First published September 4, 2003 10.1152/ ajpheart.00588.2003 diastolic function during atrial fibrillation (AF) remains poorly understood due to the complex interaction of factors and beat-to-beat variability. The purpose of the present study was to elucidate the physiological determinants of beat-to-beat changes in LV diastolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Few studies have reported interbeat changes of diastolic function. Tabata et al (22) reported that LV relaxation depended on the systolic LV pressure during the preceding heartbeat in an experiment using dogs that underwent thoracotomy under anesthesia. In AF patients whose atrial systolic waves are absent, it is difficult to evaluate diastolic function based on transmitral flow velocity waveforms.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported interbeat changes of diastolic function. Tabata et al (22) reported that LV relaxation depended on the systolic LV pressure during the preceding heartbeat in an experiment using dogs that underwent thoracotomy under anesthesia. In AF patients whose atrial systolic waves are absent, it is difficult to evaluate diastolic function based on transmitral flow velocity waveforms.…”
Section: Discussionmentioning
confidence: 99%
“…7 Averaging some diastolic indices using Doppler echocardiography in multiple consecutive heart beats is tedious and cumbersome, and its routine application is often difficult in busy clinical scenarios. 8,9 In sinus rhythm, mitral inflow velocities usually consist of 2 forward flow velocities: the early rapid filling wave (E wave) and A wave. However, mitral inflow may have additional forward flow during mid-diastole.…”
mentioning
confidence: 99%
“…Time invariance is assured by study design but although SV, EDV, and EDP are quasi-linearly related within the physiological range as expected by Frank-Starling's law (37), essentially every nature process is nonlinear in nature so this model is clearly an approximation to reality. Indeed, several new highly-demanding computational-based methods have expanded the assessment of the correlation between input and output variables in the cardiovascular system to nonlinear relationships by various approaches (30).…”
Section: Methodsmentioning
confidence: 93%